PENENTUAN KOEFISIEN SERAP BUNYI PAPAN PARTIKEL DARI LIMBAH PELEPAH KELAPA SAWIT - Abdi Setia Putra (Jurnal Surya Teknika, 2020)
The study is done to determine the characteristics of the material absorbs the particle board made of palm oil to the midrib 0,6 0,4 density and 0,9 gr / cm3 adhesive with variations 15% and 20 % adhesive urea and formaldehyde in use . Frequencies used is 125,250,500,1000 , and 1200 hz . Value the absorption of sample made showing the price qualified according to sample ISO 11654 to classify it as a silencer and included in a category class the quality c. Research aims to understand characteristic of the coefficients employ the board particles of material midrib palm. Employ procedure test the were based on standard ASTM E1050-98 using the of tube impedance 2 microphone .Sample of measuring diameter ± 99 mm. value density large frequency ( hz ) good affect on value the coefficients employ the ( α ) . Employ a value the will decrease in frequency 1000-1200hz and in density gr 0,9 / cm3.